2022
DOI: 10.1097/adm.0000000000000912
|View full text |Cite
|
Sign up to set email alerts
|

A Low-threshold Comprehensive Shared Medical Appointment Program for Perinatal Substance Use in an Underserved Population

Abstract: Objectives: We describe retention in care, medication for opioid use disorder (MOUD) prescribing, and urine toxicology outcomes of a comprehensive perinatal shared medical appointment model that combined medication, group-based counseling, and recovery supports. Methods: We conducted a retrospective study of program retention between 11/1/16 and 3/31/20 in pregnant and postpartum women with substance dependence or use disorder. Disengagement reasons, MOUD prescribing, and urine toxicology were abstracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Historically, SUD and IPV are predictors of poor retention in mental health programming, particularly when combined with underlying severe psychopathology -such as severe perinatal anxiety [54][55][56][57][58][59][60]. In our study, because IPV and substance use risk did not predict attrition from the program, this highlights the importance of accessible, patient-facing mental healthcare for these particularly vulnerable patient populations.…”
Section: Discussionmentioning
confidence: 63%
“…Historically, SUD and IPV are predictors of poor retention in mental health programming, particularly when combined with underlying severe psychopathology -such as severe perinatal anxiety [54][55][56][57][58][59][60]. In our study, because IPV and substance use risk did not predict attrition from the program, this highlights the importance of accessible, patient-facing mental healthcare for these particularly vulnerable patient populations.…”
Section: Discussionmentioning
confidence: 63%
“…Historically, substance use disorder (SUD) and IPV are predictors of poor retention in mental health programming, particularly when combined with underlying severe psychopathology, such as severe perinatal anxiety [61][62][63][64][65][66][67]. In our study, because IPV and substance use risk did not predict attrition from the program, this highlights the importance of accessible, patient-facing mental healthcare for vulnerable patient populations.…”
Section: Discussionmentioning
confidence: 77%
“…Prior work has suggested that collaboration and shared decision making between providers in the perinatal period can encourage treatment for both psychiatric conditions and OUD in this critical time period ( Raffi et al, 2021 ). In addition, prior work has shown greater treatment engagement among patients with OUD who are receiving care that includes wraparound services that involves behavioral health and care coordination ( Ganetsky et al, 2022 ). Although prior work has called attention to the need for integrated care, the evidence of the efficacy of this care remains limited.…”
Section: Discussionmentioning
confidence: 99%